Desenvolvimento de um probiótico recombinante contendo a Proteína “3” de superfície de merozoíto de Plasmodium falciparum e avaliação imunológica em murinos - (:unkn) unknown (Universidade Federal do Amazonas, 2022)
Malaria is a public health problem widely distributed in tropical and subtropical regions of the world. In Brazil, the disease still has high numbers of cases, which Plasmodium falciparum (P. falciparum) is responsible for the most severe form of the disease. One of the alternatives for controlling the infection would be the development of a vaccine. Currently, there is still no vaccine for malaria with 100% protection. An important step in the development of a vaccine, in addition to the identification of the antigen, is to evaluate how the antigen will be presented, as well as the immunostimulatory effect of the formulation components (immunostimulants). One of the immunostimulation and presentation methods that has received attention is based on the use of Bacillus subtilis spores . Furthermore, it has been observed that they can act as adjuvant vaccine particles, promoting the elevation of the humoral response after coadministration with antigens either coupled or integrated to the surface of these spores. Thus, the objectives of this work were to produce antibodies against merozoite surface protein 3 (MSP3) of Plasmodium falciparum using spores of B. subtilis recombined, in addition to standardizing a methodology for quantification of spores by flow cytometry . A spore quantification methodology was standardized in which Trucount Beads were used together with a double labeling of the spores with ethidium bromide and fluorescent antibody, the spores were submitted to flow cytometry reading. Applying the methodology, a greater accuracy in the quantification of spores was obtained, in addition to a more reliable analysis of the coupling of the fluorescent antibody on the surface of the spores. The construction of the recombinant B. subtilis strain was performed by targeting due to fusion with the CotC coat protein. Protein expression on the spore surface was performed by immunoblot. Balb/C mice were immunized with the recombinant spores by nasal and oral route and the collected sera were analyzed by indirect ELISA. As a result, it was observed that both orally and nasal immunized mice showed stimulation of anti-PfMSP3 IgG, which was higher in the oral route. In addition, the spores were able to maintain circulating IgG titers for 250 days, triggering a predominantly Th1 immune response profile. With the promising results presented in this work, B. subtilis spores can be a great tool to be applied in future malaria vaccines.
Keywords: Parasitologia; 2.08.04.00-8; Malária; Plasmodium falciparum; msp3; Bacillus subtilis; Esporos